DEFENSE MECHANISMS OF HUGH GLASS IN THE NOVEL OF MICHAEL PUNKE’S THE REVENANT: A NOVEL OF REVENGE - Fanani, Abu; Qomariyah, Sofiatul; Mufid, Nur; Thoriqussuud, Muhammad; Amiq (LP3MKIL, 2024)
This study analyzes the defense mechanisms undergone by Hugh Glass in Michael Punke’s The Revenant: a novel of revenge. Glass conducts a defense mechanism because he wants to reduce his anxiety after being left by his friends in the woods and fighting against a mother bear alone. His action of doing defense mechanisms is psychologically explainable and is also undergone by people in real life, which then becomes the reason the researcher gets interested in analyzing defense mechanisms. Using five types of anxiety by Sigmund Freud, the study shows that Glass conducts defense mechanisms: intellectualization, rationalization, reaction formation, repression, and sublimation. By intellectualization, Glass gets rid of anger, by displacement, Glass gets his target for nutrition, by rationalization, Glass gets reality, by reaction formation, Glass takes everything for granted, by repression, he does anything else more useful, by sublimation, Glass does good things instead of taking revenge. By this study, then, the researcher hopes so much that it contributes to the development of the literary study, especially in the study of the psychology of literature.